Perceived Barriers and Experiences of Parents in Performing Oral Care on Children Suffering from Cancer: A Qualitative Study - Krisnana, Ilya; Kurnia, Iqlima Dwi; Haningtyas, Dyah Puddya; Ugrasena, I.D.G; Arief, Yuni Sufyanti (International Journal of Psychosocial Rehabilitation, 2020)
Oral hygiene is one of the factors associated with dental problems, a major factor in preventing oral infections and systemic complication prevention. This study aims to explore the perceived barriers and experiences of parents in performing oral care for children suffering from cancer. The study sample consists of 16 parents of children with cancer who live in special shelters for children with cancer who have homes very far from the hospital. This study used a qualitative design through semi-structural phenomenological interviews. The data were analyzed by Colaizzi. The perceived barriers experienced by parents come from external and internal factors. External barriers originate from the condition of the child during hospitalization as related to the equipment installed, for example, the IV line, oxygen mask, etc. Internal barriers are strongly associated with concerns about the possibility of bleeding if the child is given oral care. Health education about oral care can provide an understanding and information about procedures appropriate for oral care methods for children suffering from cancer.